Real-World Safety and Efficacy Outcomes with Abiraterone Acetate Plus Prednisone or Prednisolone as the First- or Second-Line Treatment for Metastatic Castration-Resistant Prostate Cancer: Data from the Prostate Cancer Registry - Bjartell, Anders; Lumen, Nicolaas; Maroto, Pablo; Paiss, Thomas; Gomez-Veiga, Francisco; Birtle, Alison; Kramer, Gero; Kalinka, Ewa; Spaëth, Dominique; Feyerabend, Susan; Matveev, Vsevolod; Lefresne, Florence; et al. (Targeted oncology, 2021)
BACKGROUND: Despite standard-of-care androgen-deprivation therapy and an increasing number of treatment options, the mortality rate for prostate cancer remains high. Progress to metastatic castration-resistant prostate cancer (mCRPC) necessitates additional treatments. Abiraterone acetate plus prednisone or prednisolone (AAP) prolongs survival in chemotherapy-naive and docetaxel-experienced patients. OBJECTIVE: To evaluate the real-world safety and efficacy of AAP as first-line and second-line [post-docetaxel only (AAP-PD)] treatment in patients with mCRPC. PATIENTS AND METHODS: The Prostate Cancer Registry (PCR) was a prospective, international, observational study of patients with mCRPC in routine clinical practice. Men aged ≥ 18 years with confirmed mCRPC were included. Baseline characteristics, safety (treatment-emergent adverse events, treatment-emergent severe adverse events), and efficacy [progression-free survival (PFS) and overall survival (OS)] were analyzed. RESULTS: At baseline, patients who received first-line AAP (n = 754) were generally older than patients who received AAP-PD (n = 354); median age was 76 years and 70 years, respectively. However, the rate of visceral metastasis was higher in the AAP-PD cohort than in the AAP cohort (17.7% vs. 9.6%, respectively). Demographics and disease characteristics of patients with baseline cardiovascular disease were similar to those of the overall registry population. Efficacy outcomes were similar for all patients, regardless of the line of AAP therapy. For first-line AAP and AAP-PD, respectively, the median PFS was 8.9 and 5.8 months for all patients and 9.1 and 6.0 months for patients with cardiovascular comorbidities; median OS was 27.1 and 23.4 months for all patients, and 27.4 and 23.1 months for patients with cardiovascular comorbidities. There were no unexpected adverse events in any patient subgroup. CONCLUSIONS: These real-world data complement the findings from randomized controlled trials, indicating that first- and second-line AAP is well tolerated and effective in patients with mCRPC, including those with underlying CV comorbidities. TRIAL REGISTRATION NUMBER: NCT02236637, registered 8 September 2014.
Keywords: registrace; Male; mužské pohlaví; nádory prostaty rezistentní na kastraci; Abiraterone Acetate; Aged; Prostatic Neoplasms, Castration-Resistant; abirateron; Registries; Humans; lidé; Prednisone; prednison; senioři